After the Signal Came: Changes in Behavior of Village Teens Using Gadget in Hulu Jambi - Ari Sopyan; Arfan; Mursyidah Dian (International Journal of Social Sciences Review, 2020)
The research that underlies this paper aims to look at changes in adolescent behavior in the village after the proliferation of gadgets and the response of parents to changes in the behavior of these adolescents. The village of Muara Mensao, which is the location of the research, is located in the upper reaches of Jambi and only received an internet signal five years ago. Positive habits were once a part of village youth's life. Afternoon sports, cooperation, and being on the committee for a feast are three examples. Through observations and interviews with local community leaders, parents, and six teenagers, gadgets or gadgets that enter the village following the presence of an internet signal, it is recognized that it has harmed the youth of Muaro Mensao, namely: reduced social bonds and face-to-face contact with fellow teenagers, changes in interest from collective activities become online games, leading teenagers to gamble and negative content on the internet. Parents and the community have taken actions to reduce the negative impact of gadgets by: first, instilling religious values, secondly teaching discipline to their children, and thirdly giving verbal advice and warnings.